2011
DOI: 10.2169/internalmedicine.50.4354
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of an Autosomal Recessive Disorder, Gitelman's Syndrome, Across Two Generations in One Family

Abstract: Gitelman's syndrome (GS) is an autosomal recessive disorder; it is rarely inherited over several generations. A 16-year-old boy showed hypokalemia and hypocalciuria. Clinically, he was diagnosed as GS because of diuretic responsiveness to furosemide but not thiazide. Genetic testing disclosed he was a compound heterozygote (T180K/V677M) for the SLC12A3 gene. Unexpectedly, the patient's father also showed hypokalemia and hypocalciuria. The genetic analysis showed he had an L849H mutation in addition to T180K. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The assumption that GS is caused by a defect in the NCCT cotransporter in the renal distal tubule has been proven by the identification of numerous variations in the SLC12A3 gene in patients with GS [1,4,19,21]. In the present study the specific involvement of this cotransporter in the etiology of this disorder is further substantiated by the finding that the proband is homozygous for the S615L variation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The assumption that GS is caused by a defect in the NCCT cotransporter in the renal distal tubule has been proven by the identification of numerous variations in the SLC12A3 gene in patients with GS [1,4,19,21]. In the present study the specific involvement of this cotransporter in the etiology of this disorder is further substantiated by the finding that the proband is homozygous for the S615L variation.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, seven individuals heterozygous for the S615L did not have either hypokalemia or hypomagnesemia, confirming that they were asymptomatic carriers of this variation. Hypomagnesemia and hypocalciuria are found in most cases of GS, however, some cases with mutations in the NCCT do not show these conditions [19]. It is believed that hypomagnesemia causes CC by increasing formation and reducing solubility of CCP crystals [16].…”
Section: Discussionmentioning
confidence: 99%
“…2 In GS, the degree of volume contraction and the stimulation of the reninangiotensin-aldosterone axis mostly represent a milder phenotype, and plasma aldosterone levels might remain within normal range. 7 Our patient showed biochemical abnormalities, including hypokalemia, metabolic alkalosis, hypomagnesemia, hypocalciuria, and increased plasma renin and aldosterone activity, strongly suggesting that GS is a disorder usually showing minor or mild symptoms and its long-term prognosis is also extremely good. 4 Bettinelli et al 8 reported a 6-year-old girl followed for 14 years.…”
Section: Discussionmentioning
confidence: 58%
“…The prognosis of the disease is good, so antenatal diagnosis is not recommended to the patients. 7 MEFV gene encodes pyrin, a protein consisting of 781 amino acids. The association between the disease and many FMF gene mutations, such as M694V, M694I, and V726A, has been clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…If there is not any increase in the fractional excretions of sodium, chloride and potassium after thiazide is given, then the problem is thought to be in the thiazide-sensitive Na/Cl cotransporter. 13 Bettinelli and his friends stated the criteria for the diagnosis of GS as hypomagnesemia, hypokalemia and hypocalciuria. 14 BS typically emerges before the age of 6 with severe symptoms like dehydration, nephrocalcinosis and growth retardation, whereas GS usually appears at an adult age and with neuromuscular symptoms.…”
Section: Discussionmentioning
confidence: 99%